EPISTEMOLOGI NAHW TA‘LÎMÎ DALAM PERSEPEKTIF LINGUIS ARAB KONTEMPORER - Khabibi Muhammad Luthfi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
This paper amis to analyze the essence, source, approach and validity of syntax of pedagogical Arabic in the perspective of contemporary linguists. This was based on linguists who hold a classical syntax, saying renewal of pedagogical syntax in the contemporary era is not yet epistemological because it only redefines and implies classical syntax. With the philosophy approach of language education and educational linguistic theory based on library data with discourse analysis, it is found that pedagogical syntax iss Arabic grammar for learning to be proficient in speaking; derived from the Quran, hadith, poetry and syntax of classical schools and modern Arabic writing. The drafting approach is structural-behavioral with prescriptive, relevance, gradation, structural, clarity and simple principles. The methods are naqd, damj, tarjîh al-’arâ’, ziyâdah, tabwîb and ikhtishâr. The validity is pragmatic. On this basis, pedagogical syntax has its own distinct epistemology with classical syntax.